Kebebasan Berekspresi sebagai Hak Konstitusional dan Batas Konstitusionalnya: Telaah atas Pengujian Undang-Undang ITE di Mahkamah Konstitusi - Bunggati Umbu Weni; Dudik Djaja Sidarta; Fathul Hamdani; Noenik Soekorini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Freedom of expression is a constitutional right that occupies a crucial position in the structure of Indonesia's democratic rule of law, as it is guaranteed in Article 28E paragraph (2), Article 28E paragraph (3), and Article 28F of the 1945 Constitution of the Republic of Indonesia. In practice, this guarantee often clashes with restrictive policies through the Electronic Information and Transactions Law, particularly in provisions on insults, defamation, and hate speech in the digital space that have the potential to lead to multiple interpretations and criminalization of criticism. This article aims to analyze the position of freedom of expression as a constitutional right, the constitutional limits of its restrictions, and the development of the Constitutional Court's interpretation in testing the ITE Law, particularly through Decision Number 50/PUU-VI/2008 and Decision Number 105/PUU-XXII/2024. The research uses normative legal methods with statutory, conceptual, and case approaches. The results of the study indicate that the direction of the Constitutional Court's interpretation has evolved from a more permissive approach to the criminalization of expression to a more restrictive, proportional, and protective interpretation of citizens' constitutional rights in the digital space.